Pengendalian Produk Pakaian Untuk Meminimasi Defect Dengan Menggunakan Metode Statistical Quality Control pada trit adventure - Elvira Djalil; Ida Ayu Nuh Kartini (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
Product Quality Is A Crucial Factor In Maintaining A Company's Competitiveness, Especially In The Apparel Industry. This Research Was Conducted At Trit Adventure, A Company Engaged In The Production Of Outdoor Equipment, Which Faces Quality Issues Such As Untidy Stitching, Damaged Screen Printing, And Inconsistent Sizing. The Aim Of This Study Is To Minimize Defective Products Through The Application Of The Statistical Quality Control (SQC) Method.The Methods Used Include P-Chart, Pareto Diagram, And Fishbone Diagram To Analyze The Main Causes Of Defects And Determine Appropriate Corrective Actions. The Results Show That Human Factors, Particularly Employee Negligence, Are The Dominant Cause Of Product Defects.The Implementation Of SQC Has Proven To Assist The Company In Identifying Critical Points In The Production Process, Reducing Defect Rates, And Improving Operational Efficiency. Through Better Quality Control, Trit Adventure Can Maintain Product Quality Standards And Enhance Customer Satisfaction In The Competitive Outdoor Equipment Market.